2016
DOI: 10.1038/srep23768
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish biosensor for toxicant induced muscle hyperactivity

Abstract: Robust and sensitive detection systems are a crucial asset for risk management of chemicals, which are produced in increasing number and diversity. To establish an in vivo biosensor system with quantitative readout for potential toxicant effects on motor function, we generated a transgenic zebrafish line TgBAC(hspb11:GFP) which expresses a GFP reporter under the control of regulatory elements of the small heat shock protein hspb11. Spatiotemporal hspb11 transgene expression in the musculature and the notochord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Klüver et al reported similar results in hspb11 expression with propoxur and also demonstrated that hspb11 expression is muscle activity dependent, which is modulated by AChE inhibitors [89]. A lack of hspb11 upregulation in response to an AChE inhibitor in embryos significantly interferes with neuromuscular transmission between motor neurons and muscle fibers [90] and could begin to explain some of the behavioral alterations witnessed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Klüver et al reported similar results in hspb11 expression with propoxur and also demonstrated that hspb11 expression is muscle activity dependent, which is modulated by AChE inhibitors [89]. A lack of hspb11 upregulation in response to an AChE inhibitor in embryos significantly interferes with neuromuscular transmission between motor neurons and muscle fibers [90] and could begin to explain some of the behavioral alterations witnessed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to heat stress, this survival-promoting response can be induced by aging, protein-folding diseases, and exposure to toxic chemicals (Scheff Jeremy, Stallings Jonathan, Reifman, & Rakesh, 2015). The heatshock promoter driving GFP TgBAC(hspb11:GFP) has been used as a surrogate marker to identify the tissue-specific effects of pesticides (Shahid et al, 2016). This recent study highlights how different cell types are impacted by exposure to the same stressor.…”
Section: Zebrafish: Testing the Waters For Toxicantsmentioning
confidence: 99%
“…Zebrafish embryos were exposed to a number of different pesticides from 9 to 48 hours postfertilization (hpf) and examined for induction of the TgBAC(hspb11:GFP) transgene and muscle integrity. This transgene largely is activated in the muscle and notochord of embryos exposed to pesticides, however, the magnitude of the response varied: azinphosmethyl had a moderate effect on induction of the hspb11 transgene and also only modestly affected muscle integrity, whereas, galanthamine caused severe disruption of muscle integrity and strongly activated the hspb11 promoter (Shahid et al, 2016). Interestingly, the transgene remained active in muscle tissue up to 48 h after the pesticides were removed, indicating the long-lasting effects of toxin exposure on these cells.…”
Section: Zebrafish: Testing the Waters For Toxicantsmentioning
confidence: 99%
“…These genetically modified lines play the role of excellent biosensors which, due to the use of specific genetic regulatory elements to drive the expression of fluorescent proteins, provide both the possibility for demonstration of the tissue-specific mode of toxicants’ action and the presence of target classes of pollutants [88,92,93]. Moreover, biosensors enable assessment of different compounds’ toxicity at relatively low doses corresponding to ecologically relevant concentrations.…”
Section: Biosensors and Their Applications For Toxicological Researchmentioning
confidence: 99%
“…Recently, an in vivo biosensor system with a quantitative readout for assessment of toxicants’ influence on motor function was successfully developed [93]. This transgenic zebrafish line TgBAC ( hspb11:GFP ) expresses a GFP reporter under the control of regulatory elements of the small heat shock protein hspb11 , which is up-regulated specifically by chemicals that interfere with motor function [94].…”
Section: Biosensors and Their Applications For Toxicological Researchmentioning
confidence: 99%